The Effect of Financial Technology on MSMEs Performance: The Mediating Role of Financial Inclusion - Usman, Mohammed Hamidu; Muhammad, Sallau Muhammad; Kassim, Sulaiman Ibrahim (FUDMA Journal of Accounting and Finance Research [FUJAFR], 2025)
Financial technology (fintech) has made financial services more accessible to small and medium enterprises (SMEs) by offering digital payment methods and alternative financing platforms. Because of this advancement, financial inclusion has improved, making it easier for SMEs to get loans and handle transactions effectively. The purpose of the study is to empirically investigate the effect of fintech on SME performance in Jigawa State and whether financial inclusion can mediate the relationship. A descriptive research design approach was used to sample 352 SMEs in Jigawa State, Nigeria, using a convenient sampling technique. A structural equation modelling technique using Smart PLS v.4.1 software was used to test inferential statistics, and SPSS v.23 software was used to test descriptive statistics. The specific indirect effects statistics show that among the dimensions of fintech, Perceived Usefulness (PUS) and Perceived Ease of Use (PEU) were found to mediate between financial inclusion and SME performance, whereas Perceived Trust (PTT) and Responsiveness (RPN) have no mediating effect. The result of the path coefficient indicates that PUS, PEU, and PTT have a positive and significant influence on financial inclusion, while RPN does not. Among the fintech dimensions, PUS & RPN have a positive and significant effect on SME performance, while PEU & PTT don’t. The study also found that financial inclusion significantly predicts SME performance. The government should support fintech companies to develop new business solution apps/software since their perceived usefulness is recognised by SMEs.